Identification of a Novel Intron and 4 Polymorphisms in the Gene Encoding the γ Subunit of the Epithelial Sodium Channel - XU, XIN; NIU, TIANHUA; CHEN, CHANGZHONG; YANG, JIANHUA; FANG, ZHIAN; XU, XIPING (Human biology, 1999)
The amiloride-sensitive epithelial sodium channel is a highly selective sodium channel that constitutes the rate-limiting step of sodium reabsorption in distal nephrons. It consists of at least 3 subunits (Table 2. Continued, â, and ã) of similar structure and plays an important role in sodium and fluid homeostasis. Defects of this channel have been critically implicated in Liddle syndrome (pseudoaldosteronism) and pseudohypoaldosteronism type 1. A sample of 48 individuals from 23 nuclear families was selected from Anhui, China. We sequenced 12 exons and flanking intronic sequences and discovered a new 207-bp intron located in the previously described exon X of Thomas et al. (1996). In addition, 4 novel single nucleotide polymorphisms were identified; 3 were in exon 3 and 1 was in exon 13. Furthermore, 2 base substitutions in exon 13 were present in all the Chinese subjects compared with the published European SCNN1G DNA sequence.